2015
DOI: 10.1177/0885328215572196
|View full text |Cite
|
Sign up to set email alerts
|

Composition-property relationships for radiopaque composite materials: pre-loaded drug-eluting beads for transarterial chemoembolization

Abstract: The purpose of this study was to synthesize and optimize intrinsically radiopaque composite embolic microspheres for sustained release of doxorubicin in drug-eluting bead transarterial chemoembolization. Using a design of experiments approach, 12 radiopaque composites composed of polylactic-co-glycolic acid and a radiopaque glass (ORP5) were screened over a range of compositions and examined for radiopacity (computed tomography) and density. In vitro cell viability was determined using an extract assay derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recent improvements of TACE, including the introduction of new types of embolics (PEG microspheres), have increased tumor response in CRC-LM patients [23,24]. Some type of beads (LUMI) incorporate an imaging agent and can be loaded with a chemotherapeutic drug and can be visualized during TACE and in follow-up imaging [25][26][27].…”
Section: Debiri Activity and Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent improvements of TACE, including the introduction of new types of embolics (PEG microspheres), have increased tumor response in CRC-LM patients [23,24]. Some type of beads (LUMI) incorporate an imaging agent and can be loaded with a chemotherapeutic drug and can be visualized during TACE and in follow-up imaging [25][26][27].…”
Section: Debiri Activity and Clinical Applicationmentioning
confidence: 99%
“…In the past decade, several efforts have been made to improve TACE tolerability, including drug dosage adjustments, incremental experience of interventional radiologist, introduction of new type of drugs and microspheres to obtain a more precise and selective treatment [23][24][25][26][27].…”
Section: Debiri-related Side Effectsmentioning
confidence: 99%
“…suggest that radiopacity values comparable to those obtained herein may provide a method to evaluate the spatial distribution of particles using either cone beam CT immediately postembolization or with conventional CT scan during follow-up. 54 Using mice, Meng et al. show that subcutaneously implanted microspheres with radiopacity values approximately equal to 4250 HU were visible using X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Kilcup et al suggest that radiopacity values comparable to those obtained herein may provide a method to evaluate the spatial distribution of particles using either cone beam CT immediately postembolization or with conventional CT scan during follow-up. 54 Using mice, Meng et al show that subcutaneously implanted microspheres with radiopacity values approximately equal to 4250 HU were visible using X-ray. 55 Lee et al demonstrated that tantalum containing nanoparticles with radiopacity values below 1000 HU when suspended in water caused enhanced visibility of blood vessels, spleen, and liver in a rat using CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have investigated such radiopaque DEBs. For example, 2,3,5-triiodobenzaldehyde has been coupled to the backbone of polyvinyl alcohol to produce DC Bead LUMI 17 - 20 , whereas radiopaque composites of poly lactic-co-glycolic acid and a radiopaque glass have also been produced 21 . However, the synthesis of such copolymers or radiopaque glass is rather complicated, and so there is need for a universal method to economically and easily produce radiopaque DEBs from readily available materials.…”
Section: Introductionmentioning
confidence: 99%